Laboratory Animal Welfare Meets Human Welfare: A Cross-Sectional Study of Professional Quality of Life, Including Compassion Fatigue in Laboratory Animal Personnel - LaFollette, Megan R.; Riley, Megan C.; Cloutier, Sylvie; Brady, Colleen M.; O'Haire, Marguerite E.; Gaskill, Brianna N. (Frontiers in Veterinary Science, 2020)
Laboratory animal personnel may experience significant stress from working with animals in scientific research. Workplace stress can be assessed by evaluating professional quality of life, which is comprised of compassion fatigue (i.e., burnout and secondary traumatic stress) and compassion satisfaction. This research aimed to explore the associations between risk factors and professional quality of life in laboratory animal personnel. In a cross-sectional, convenience sample design, laboratory animal personnel were recruited from widespread online promotion. A total of 801 personnel in the United States or Canada completed an online survey regarding professional quality of life, social support, euthanasia, enrichment, stress/pain levels, and human-animal interactions. Participants worked in a wide range of settings (e.g., industry, academia), research types (e.g., basic, applied, regulatory), species (e.g., non-human primates, mice), and roles (e.g. animal caretaker, veterinarian). Data were analyzed using general linear models. Personnel who reported higher compassion fatigue also reported lower social support, higher animal stress/pain, higher desire to implement more enrichment, and less control over performing euthanasia (p’s<0.05). Higher burnout was associated with less diverse/frequent enrichment, using physical euthanasia methods, and longer working hours. Higher secondary traumatic stress was associated with more relationship-promoting human-animal interactions (e.g., naming animals) and working as a trainers (p’s<0.05). Higher compassion satisfaction was associated with higher social support, less animal stress/pain, and more human-animal interactions (p’s<0.05). Surprisingly, neither personnel’s primary animal type (e.g., non-human primates, mice) nor frequency of euthanasia (e.g., daily, monthly) were associated with professional quality of life (p’s>0.05). Our findings show that the professional quality of life of laboratory animal personnel is associated with several factors. Personnel reporting poorer professional quality of life also reported less social support, higher animal stress/pain, less enrichment diversity/frequency and wished they could provide more enrichment, using physical euthanasia, and less control over performing euthanasia. Poorer professional quality of life was also seen in personnel working as trainers, at universities, and longer hours. This study contributes important empirical data that may provide guidance for developing interventions (e.g., improved social support, decreased animal stress, increased animal enrichment diversity/frequency, greater control over euthanasia) to improve laboratory animal personnel’s professional quality of life.